(untitled) (Research, Society and Development, 2021)
The natural products extracted from plants are part of traditional medicine and are also therapeutic possibilities for treating many diseases. Recently, its use in the development of new drugs has shown much visibility for its efficiency and few adverse effects. Essential oils extracted from medicinal plants are indicated to treat numerous diseases due to their antimicrobial, antiviral, antimutagenic, anticancer, antioxidant, anti-inflammatory, immunomodulatory, and antiprotozoal properties. Among essential oils, lavender essential oil stands out for having several important pharmacological properties. This review detailed the main studies on essential oils from different species of lavender and obtained a valuable collection on all their pharmacological, medicinal and toxicological potential. In this context, we evaluated lavender essential oil as a promising substance that can help treat several diseases. We provide some evidence and an overview of the potential therapeutic effect of lavender essential oil to guide new research.